Vacation Study Abroad - Institute of International Education, New York, NY.; Howard, E. Marguerite; Institute of International Education, New York, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
A guide to summer study abroad is presented with information on how to plan rewarding summer study and travel overseas. Concise descriptions of over 1300 postsecondary study programs worldwide (in over 65 countries) sponsored by U.S. and foreign universities and institutions are included with details on program sponsor and name, location, dates, subjects, credit, eligibility, instruction, highlights, costs, housing, deadline, and contacts. The focus is on programs worldwide and in Africa (south of the Sahara), Asia and Oceania, Europe, Middle East and North Africa, and the Western Hemisphere. Programs are arranged first by the geographical region of the world, and each region is subdivided alphabetically by country and then by city, province, area, or island. Within each city subsection, the arrangement is alphabetical by the names of the sponsoring institutions. Two appendices offer consortia and suggestions on how to read study-abroad literature. Sponsoring institutions and fields of study are indexed. (SM)
Availability: Institute of International Education Books, 809 United Nations Plaza, New York, NY 10017 ($22.95).
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Students; Foreign Countries; Global Approach; Higher Education; International Cooperation; International Educational Exchange; Planning; Reference Materials; Study Abroad; Summer Programs; Summer Schools; Tourism; Travel; Guides, Non-Classroom.